Cleft lip and palate: An overview - Kannan, Thirumulu Ponnuraj; Mokhtar@Makhtar, Khairani Idah; Mohamad Nasir, Nurul Fatihah (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2017)
This book gives a brief introduction on craniofacial development with special emphasis on cleft lip and palate. Anomalies in embryological development varies and, today, different techniques are employed for diagnosing the genetic abnormalities related to craniofacial defects. Bearing that in mind, this book was written with the aim of describing the fundamentals in cleft lip and palate and selected laboratory techniques that are applied in diagnosing and analysing these defects.